ANALISIS PENERAPAN TARIF PROGRESIF TERHADAP PENERIMAAN BEA BALIK NAMA KENDARAAN BERMOTOR DI KANTOR SAMSAT MEDAN UTARA - Benny Suranta Barus; Alistraja Dison Silalahi; M.Rizaldi Wibowo (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2020)
This study aims to determine whether the application of progressive tariffs applied at the North Medan Samsat Office is in accordance with North Sumatra regional regulations and to analyze BBNKB revenues after the latest rates are applied. The research method used in this research is descriptive qualitative using primary data and secondary data with data collection techniques through interviews, observation and documentation. The results of this study indicate that the North Medan Samsat Office has implemented a progressive motorized tariff in accordance with the Law and Regional Regulation No. 1 of 2015. The results of the application of progressive lower tariffs prove that the annual motor vehicle tax revenue can increase. Based on this research it can also be seen that the application of the latest BBNKB tariffs annually increases the acceptance of Motorized Vehicle Transfer Fee receipts annually.